Effect of Drying Temperature Variation on the Antioxidant Activity Ethanol Extract of Cocoa Bean (Theobroma cacao L.) with ABTS [2,2-azino-bis(3-ethylbenzotiazolin-6-sulphonic acid)] Method - Wibawa, Agung Ari Chandra; Pramitha, Dewa Ayu Ika; Sanjiwani, Ni Made Sukma; Rahadi, I Wayan Surya; Arandika, I Wayan Wisma (Hydrogen: Jurnal Kependidikan Kimia, 2025)
Plants contain chemical compounds that are used as natural medicinal ingredients as antioxidants and have the potential to act as free radicals. Cocoa plants are rich in polyphenols such as flavanols, which have antioxidant and anti-inflammatory properties against degenerative diseases. The aim of the research is to determine whether variations in drying temperature of cocoa bean ethanol extract (Theobroma cacao L.) affect antioxidant activity. This research is in the form of experimental research carried out in a laboratory. The drying method uses an oven for 8 hours at temperatures of 40, 50, and 60ºC. The dried cocoa beans were extracted using the maceration method using ethanol solvent. Antioxidant analysis in this study used the ABTS [2,2-azino-bis(3-ethyl-benzothiazolin-6-sulphonic acid)] method with a microplate reader at a wavelength of 630 nm. The value used to determine antioxidant activity was the IC50 value. All samples BKS 40, BKS 50, and BKS 60 had air contents of 49.34%, 32.7%, and 24.32%. The results of this study prove the antioxidant activity of cocoa bean ethanol extract (BKS 40, 50, and 60) is included in the strong category with IC50 values 86, 88, and 71 μg/mL, respectively. The results prove that temperature does not affect antioxidant activity.